Integrated time-series biochemical, transcriptomic, and metabolomic analyses reveal key metabolites and signaling pathways in the liver of the Chinese soft-shelled turtle (Pelodiscus sinensis) against Aeromonas hydrophila infection - Ji, Liqin; Chen, Chen; Zhu, Junxian; Hong, Xiaoyou; Liu, Xiaoli; Wei, Chengqing; Zhu, Xinping; Li, Wei (Frontiers in Immunology, 2024)
Aeromonas hydrophila, a bacterium widely distributed in the natural environment, causes multiple diseases in various animals. Exploring the mechanism of the host defense against A. hydrophila can help develop efficient strategies against Aeromonas infection. Herein, we investigated the temporal influence of A. hydrophila on the Chinese soft-shelled turtle, an economically important species, at the biochemical, transcriptomic, and metabolomic levels. Plasma glucose, an antimicrobial enzyme (alkaline phosphatase, AKP), two oxidative biomarkers including catalase (CAT) and malonaldehyde (MDA), and two aminotransferases comprising glutamic oxalacetic transaminase (GOT) and glutamate pyruvate transaminase (GPT), were analyzed at 0, 12, 24, 48, and 96 hours post infection (hpi). The contents or activities of these plasma parameters were significantly increased at 24 hpi and declined at 96 hpi, indicating that 24 and 96 hpi were two important time points during infection. Then, we integrated the hepatic transcriptome and metabolome of Chinese soft-shelled turtles responding to A. hydrophila at 0, 24, and 96 hpi. Totals of 3121 and 274 differentially expressed genes (DEGs) from the transcriptome while 74 and 91 differentially abundant metabolites (DAMs) from the metabolome were detected at 24 and 96 hpi.The top DEGs at 24 hpi included Ccl2,